Multimodal assessments of preterm temperament across the first year of life: Continuity, stability, and moderation by country of origin and infant age. Issue 2 (14th February 2022) - Spinelli, Maria; Bornstein, Marc H.; Putnick, Diane L.; Shah, Prachi E.
Abstract: There is limited research regarding the continuity, stability, and role of country of origin in preterm infant temperament across the first year of life. This prospective longitudinal study examined patterns of mean‐level continuity and individual‐differences stability of select scales of temperament at 6 and 12 months in preterm infants from three countries, Chile ( n = 47), United Kingdom ( n = 44), and United States ( n = 50). Temperament was assessed with the Infant Behavior Questionnaire and observed using the Bayley Behavior Rating Scale. Continuity and stability across infant age, country effects, and interactions of country and age on preterm infant temperament were examined. Chilean mothers rated infants higher in soothability, duration of orienting, and orientation/engagement compared with mothers from the United Kingdom and/or United States. Continuity of temperament from 6 to 12 months varied by country: Chilean mothers reported increasing smiling and laughter and activity level from 6 to 12 months, and mothers from the United Kingdom reported decreasing smiling and laughter and increasing fear from 6 to 12 months. Infant temperament was stable in all three countries. Correlations evidenced low concordance between maternal reports and examiner observations of infant temperament at 12 months. However, among Chilean infants, higher maternal reported activity level was associated with higher examiner observed orientation/engagement score. Resumen: Hay una limitada investigación acerca de la continuidad, la estabilidad y el papel del país de origen en el temperamento de infantes nacidos prematuramente a lo largo del primer año de vida. Este potencial estudio longitudinal examinó patrones de continuidad en el promedio de nivel y las diferencias individuales en cuanto a la estabilidad de selectas escalas de temperamento a los 6 y 12 meses en infantes prematuros de tres países, Chile (n = 47), Reino Unido (n = 44) y Estados Unidos (n = 50). El temperamento se evaluó con el Cuestionario de Comportamiento del Infante y el mismo se observó usando la Escala de Puntuación del Comportamiento de Bayley. Se examinaron la continuidad y la estabilidad a lo largo de la edad del infante, los efectos del país, así como las interacciones entre país y edad en el temperamento de los infantes prematuros. Las madres chilenas evaluaron a sus infantes con más altos puntajes en cuanto a posibilidad de tranquilizarlos, duración de orientarlos y la orientación/participación en comparación con madres del Reino Unidos y/o de Estados Unidos. La continuidad de temperamento de los 6 a 12 meses varió según el país: las madres chilenas reportaron aumento en la sonrisa y la risa, y el nivel de actividad de los 6 a 12 meses, y las madres del Reino Unido reportaron una disminución en la sonrisa y la risa, y un aumento en el temor de los 6 a 12 meses. El temperamento del infante fue estable en los tres países. Las correlaciones son evidencia de la concordancia entre los reportes maternos y las observaciones del examinador del temperamento del infante a los 12 meses. Sin embrago, entre los infantes chilenos, el más alto nivel de actividad reportado por las madres se asoció con un más alto puntaje del examinador en cuanto a la observada orientación/participación. Résumé: Nous n'avons que des recherches limitées sur la continuité, la stabilité et le rôle du pays d'origine dans le tempérament du bébé prématuré au fil de la première année de la vie. Cette étude longitudinale prospective a examiné les modèles de continuité au niveau moyen et la stabilité des différences individuelles de certaines échelles de tempérament à 6 et à 12 mois chez les enfants prématurés de trois pays, le Chili (n = 47), le Royaume Uni (n = 44) et les Etats‐Unis d'Amérique (n = 50). Le tempérament a été évalué au moyen du Questionnaire du Comportement du Nourrisson et observé en utilisant l'Echelle de Bailey d'Evaluation du Comportement du Nourrisson. La continuité et la stabilité au travers de l'âge du nourrisson, les effets du pays et les interactions du pays et de l'âge sur le tempérament du bébé prématuré ont été examinés. Les mères chiliennes ont évalué leurs bébés plus haut pour ce qui concernait la capacité à être calmé, la durée de l'orientation et l'orientation/l'engagement par comparaison aux mères du Royaume Uni et/ou des Etats‐Unis. La continuité du tempérament de 6 à 12 mois a varié par pays: les mères chiliennes ont fait état de plus de sourires et de rires et d'un niveau d'activité plus élevé de 6 à 12 mois et les mères du Royaume Uni ont fait état d'une décroissance des sourires et des rires et d'une plus grande peur de 6 à 12 mois. Le tempérament du nourrisson était stable dans les trois pays. Les corrélations ont montré une concordance faible entre les rapports maternels et les observations de l'examinateur du tempérament du nourrisson à 12 mois. Cependant, chez les enfants chiliens, un niveau d'activité plus élevé rapporté par la mère était lié à un score d'orientation/d'engagement observé plus élevé de la part de l'examinateur. Zusammenfassung: Multimodale Beurteilungen des Temperaments von Frühgeborenen im ersten Lebensjahr: Kontinuität, Stabilität und Moderation durch Herkunftsland und Säuglingsalter Es gibt nur wenige Untersuchungen zur Kontinuität, Stabilität und Rolle des Herkunftslandes beim Temperament von Frühgeborenen im ersten Lebensjahr. Diese prospektive Längsschnittstudie untersuchte 6 und 12 Monate nach der Geburt mithilfe ausgewählter Temperamentsskalen durchschnittliche Kontinuitätsmuster und individuelle Unterschiede in Stabilität bei Frühgeborenen aus drei Ländern: Chile (n = 47), Vereinigtes Königreich (n = 44) und Vereinigte Staaten (n = 50). Das Temperament wurde mit dem „Infant Behavior Questionnaire" erfasst und mit der „Bayley Behavior Rating Scale" beobachtet. Untersucht wurden Kontinuität und Stabilität über das Alter des Säuglings, Ländereffekte und Interaktionen zwischen Land und Alter im Effekt auf das Temperament des Frühgeborenen. Chilenische Mütter bewerteten ihre Säuglinge in den Bereichen Beruhigungsfähigkeit, Dauer der Orientierung und Orientierung/Engagement besser als Mütter aus dem Vereinigten Königreich und/oder den Vereinigten Staaten. Die Kontinuität des Temperaments im Alter von 6–12 Monaten variierte je nach Land: Chilenische Mütter berichteten zunehmendes Lächelnund Lachen und ein höheres Aktivitätsniveau im Zeitraum von 6 bis 12 Monaten, während Mütter aus dem Vereinigten Königreich abnehmendes Lächeln und Lachen und zunehmende Angst im Zeitraum von 6 bis 12 Monaten berichteten. Das Temperament des Säuglings war in allen drei Ländern stabil. Korrelationen zeigten im Alter von 12 Monaten eine geringe Übereinstimmung zwischen den Berichten der Mütter und den Beobachtungen der Untersuchenden zum kindlichen Temperament. Bei den chilenischen Säuglingen war jedoch ein höheres selbstberichtetes Aktivitätsniveau der Mutter mit einem höheren beobachteten Wert für Orientierung/Engagement assoziiert. 抄録: タイトル 生後1年にわたる早産児の気質に関する多軸評価 出生国別および乳幼児の月齢別による気質の継続性 、安定性、および調整力 要旨 早産児の気質の生後1年間における継続性と安定性、および出生国の役割に関する研究は限られている。本研究では、3カ国の早産児を対象に、生後6～12カ月における気質の継続性と安定性のパターンを調べ、出生国別による調整力を検証した。チリ (47名) 、イギリス (44名) 、アメリカ (50名) から母親と早産児の母子を募集し、前向き縦断研究デザインを実施した。気質は6カ月時と12カ月時に乳児行動質問票によって評価され、12カ月時には行動評価尺度によって観察された。母親の気質に関する報告について、乳児の年齢による継続性と安定性、国による違い、国と乳児の年齢の交互作用が検討された。また, 母親が報告した気質と実験室で評価した12カ月時点の気質との相関を調べた.気質の選択尺度得点は国によって異なり、チリの母親と英国や米国の母親とは比較して違いがあると報告された。乳児の気質はどの国でもほぼ安定していたが、出生国と年齢が乳児の気質に交互作用を及ぼし、6–12ヶ月の気質の継続性は国によって異なることがわかった。結果は、文化的な観点で解釈される。 摘要: 关于在出生后第一年早产儿气质中原籍国的连续性、稳定性和作用的研究有限。这项前瞻性纵向研究考察了来自智利 (n = 47)、英国 (n = 44) 和美国 (n = 50) 这三个国家的早产儿在 6 个月和 12 个月时气质量表的平均水平连续性和个体差异稳定性的模式。气质通过"婴儿行为问卷"进行评估, 并使用"贝利行为评定量表"进行观察。考察了婴儿年龄、原籍国以及原籍国与年龄相互作用的连续性和稳定性对早产儿气质的影响。与英国或美国的母亲相比, 智利母亲对婴儿的易安抚性、持续定向、定向或参与能力的评分更高。6–12个月的气质连续性因原籍国而异:智利母亲报告说, 6–12个月的微笑和大笑以及活动性水平有所增加;而英国母亲报告说, 6–12个月的微笑和大笑减少, 害怕增加。三个国家的婴儿气质都很稳定。相关性分析表明, 母亲的报告与检查员对12个月婴儿气质的观察之间的一致性较低。然而, 在智利婴儿中, 母亲报告的活动性水平越高, 检查员观察到的定向或参与能力得分越高。 ملخص: التقييمات متعددة الوسائط لمزاج الخدج عبر السنة الأولى من العمر: الاستمرارية ، والاستقرار ، والاعتدال حسب بلد المنشأ وعمر الرضيع هناك أبحاث محدودة فيما يتعلق بالاستمرارية والاستقرار ودور البلد الأصلي في مزاج الخدج عبر السنة الأولى من العمر. تناولت هذه الدراسة الطولية الاستطلاعية أنماط معدل الاستمرارية والفروق الفردية في الاستقرار من خلال مقاييس مختارة للمزاج العام في عمر 6 و 12 شهرًا عند الخدج من ثلاثة بلدان ، تشيلي (العدد = 47) ، المملكة المتحدة (العدد = 44) ، والولايات المتحدة (العدد = 50). تم تقييم الحالة المزاجية باستخدام استبيان سلوك الرضع وملاحظتها باستخدام مقياس بايلي لتقييم السلوك. وتم فحص الاستمرارية والاستقرار عبر عمر الرضيع ، ودور البلد ، والتفاعلات بين البلد والعمر على مزاج الرضع الخدج. صنفت الأمهات التشيليات الأطفال الرضع بدرجة أعلى من حيث قابلية التسكين ومدة التوجيه والمشاركة مقارنة بالأمهات من المملكة المتحدة و / أو الولايات المتحدة. تفاوتت استمرارية الحالة المزاجية من 6 إلى 12 شهرًا حسب البلد: أبلغت الأمهات التشيليات عن زيادة الابتسام والضحك ومستوى النشاط من 6 إلى 12 شهرًا ، وأبلغت الأمهات من المملكة المتحدة عن انخفاض الابتسام والضحك وزيادة الخوف من 6 إلى 12 شهرًا. وكان مزاج الرضع مستقرًا في جميع البلدان الثلاثة. أثبتت الارتباطات توافقًا منخفضًا بين تقارير الأمهات وملاحظات القائم بالفحص لمزاج الرضيع في عمر 12 شهر. ومع ذلك ، بين الرضع التشيليين ، ارتبط مستوى النشاط الأعلى المبلغ عنه من قبل الأم مع أعلى درجة للتوجه / المشاركة الملحوظة من قبل القائم بالفحص.